Genome-Wide Identification and Genetic Variations of the Starch Synthase Gene Family in Rice - Hongjia Zhang; Seong-Gyu Jang; San Mar Lar; Ah-Rim Lee; Fang-Yuan Cao; Jeonghwan Seo; Soon-Wook Kwon (Plants, 2021)
Starch is a major ingredient in rice, and the amylose content of starch significantly impacts rice quality. OsSS (starch synthase) is a gene family related to the synthesis of amylose and amylopectin, and 10 members have been reported. In the present study, a synteny analysis of a novel family member belonging to the OsSSIV subfamily that contained a starch synthase catalytic domain showed that three segmental duplications and multiple duplications were identified in rice and other species. Expression data showed that the OsSS gene family is involved in diverse expression patterns. The prediction of miRNA targets suggested that OsSS are possibly widely regulated by miRNA functions, with miR156s targeted to OsSSII-3, especially. Haplotype analysis exhibited the relationship between amylose content and diverse genotypes. These results give new insight and a theoretical basis for the improved amylose content and eating quality of rice.